Capital Structure, Profitability, Firm Size and Corporate Tax Avoidance: Evidence from Indonesia Palm Oil Companies - Ilham Condro Prabowo (Bina Nusantara University, 2020)
This study aims to provide empirical evidence about the effect of capital structure, profitability and firm size on coporate tax avoidance. The dependent variable used in this study was tax avoidance proxied by the effective tax rate (ETR), and the independent variable was capital structure (DER), profitability (ROA), and firm size. The population in this study were palm oil companies listed on the Indonesian Stock Exchange for the period 2007-2018. The samples consist of 4 palm oil companies by using purposive sampling method. The analysis technique used in this research was multiple linier regression analysis. The result shows that capital structure and profitability have positive effect on tax avoidance, while firm size have no effect on tax avoidance.